Bandwidth Improvement of EBG Resonator Antennas Using Double-Layer FSS. (30th December 2008) - Moustafa, Lina; Jecko, Bernard
Abstract : A double-layer frequency selective surface (FSS) is proposed as a means to enhance the bandwidth of an electromagnetic band gap (EBG) resonator antenna. Due to its inverted reflection phase variation and its wide selectivity bandwidth, the structure used in the radiating wall of the resonator allows increasing the radiating bandwidth of the last one. The resonator is fed by a patch feeding source placed inside the cavity at the proximity of its metallic ground. The antenna bandwidth is significantly improved by virtue of employing the double-layer FSS. Modelled results of an antenna working at 5 GHz are shown.